The Impact Study of Flexible Alternating Current Transmission System on Transient Stability of Power Systems Using MATLAB CODE and Power World Simulator - Mohamed, Elbar (2024)
The purpose of this work is the study of the influence of FACTS on transient stability of power systems using a Power World Simulator software, and the computer code transient stability code 'TRANS_STAB_CODE' 'which was created in MATLAB. We tried in the introduction of this work to provide a description on the transient stability: definition, transient stability criteria, and equations. Then we gave an overview on the modelling of FACTS in power systems, the definition and types of Flexible Alternating Current Transmission System, their schemes, and their equations, then presented the model of UPFC (Unified Power Flow Controller) as an example. Secondly, we discussed the code, 'TRANS_STAB_CODE' that was created in MATLAB by giving a description of the code and their structure with graphics windows, and then I described privately the Power World Simulator simulation software. Then we presented the test electrical network, and the results of transient stability of this network systems with the code 'TRANS_STAB_CODE' 'and with Power World Simulator where no and where there Flexible Alternating Current Transmission System. At the end, we analyzed the results of both programs in both cases: with and without Flexible Alternating Current Transmission.